2001
DOI: 10.1002/1615-9861(200109)1:9<1092::aid-prot1092>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of growth factor induced gene expression by calcium signalling: Integrated mRNA and protein expression analysis

Abstract: There is considerable indirect evidence that growth factor induced changes in the intracellular concentration of calcium play an important role in the regulation of the mammalian cell cycle. However, the precise mechanism by which this may be achieved remains unclear. Here we show that SKF-96365, an inhibitor of growth factor induced capacitative calcium entry (CCE), inhibits cell cycle progression by preventing entry into S phase. SKF-96365 changes the temporal profile of growth factor induced calcium signall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 58 publications
1
11
1
Order By: Relevance
“…A number of signaling genes whose levels of expression were altered in our studies were also found to be Ca 2ϩ regulated in other studies linking gene expression to SOCE (18,27). These include calcineurin, cAMP-dependent protein kinase catalytic-␤, FLAME-1, c-myc, frizzled homolog 7, Sine oculis homeobox homolog 2 (SIX2), and TGF-␤1.…”
Section: Changes In the Level Of Soce Have A Significant Impact On Sesupporting
confidence: 72%
See 3 more Smart Citations
“…A number of signaling genes whose levels of expression were altered in our studies were also found to be Ca 2ϩ regulated in other studies linking gene expression to SOCE (18,27). These include calcineurin, cAMP-dependent protein kinase catalytic-␤, FLAME-1, c-myc, frizzled homolog 7, Sine oculis homeobox homolog 2 (SIX2), and TGF-␤1.…”
Section: Changes In the Level Of Soce Have A Significant Impact On Sesupporting
confidence: 72%
“…Although there are a few genes in common between our study and the lymphocyte study, for the most part, SOCE appears to regulate different populations of genes in the two cell types, a possibility that we considered at the outset of the investigation (see INTRODUCTION). Compared with the data from the fibroblast study (27), the 150 genes regulated by a decrease in SOCE are much higher than the 29 genes seen to change. However, the microarray used in that study only represented 1,200 cDNA clones compared with the 22,000 cDNA clones represented on the Affymetrix microarray.…”
Section: Changes In the Level Of Soce Have A Significant Impact On Secontrasting
confidence: 57%
See 2 more Smart Citations
“…Roles for Ca 2ϩ influx have been proposed for both early and late in G 1 (7). One attractive scenario is that Ca 2ϩ influx acting through calmodulin kinase regulates the biphasic activity of MAP kinase (60). G 1 progression requires an initial peak of MAP kinase activity upon mitogen stimulation that is followed by a lower sustained level of MAP kinase activity (1,2,22).…”
Section: Discussionmentioning
confidence: 99%